Analysis of Basic Level Students' Knowledge of Hazardous and Toxic Waste - Yhoviera Farraz Muali, Aiko; Desti Ramadhani, Danila; Aulianissa Ainaya, Fadia; Muhammad, Farhan; Rachmalia, Fayza; Khairunnisa, Hasna; Hawali Abdul Matin, Hashfi (Diponegoro University, 2023)
Toxic hazardous material waste (Waste B3) is defined as waste that contains harmful and toxic substances, so that it can directly or indirectly damage the environment, disrupt health and threaten the survival of humans and other organisms. Students' awareness of B3 waste management can be seen through the level of knowledge they have. The level of knowledge is important in shaping a person's attitude or behavior towards the surrounding environment. The purpose of this study is to find out how much information or knowledge is owned by students of Sebelas Maret University (UNS) related to B3 waste management. The data analysis method used in this study is a descriptive analysis method in the form of a desriptive explanation of the data obtained about uns students' knowledge of B3 waste. The data collected in the form of primary data is conducted through interviews and questionnaires and secondary data. The results showed that the knowledge of Sebelas Maret Student University students related to B3 waste management is quite good, it can be seen through the results of questionnaires and interviews where there are 38 who already know and understand about B3 waste supported by the answers of 45 respondents who already understand the B3 waste itself, and there are 41 respondents who already know how they process B3 waste, namely by handing over B3 waste to the sewage treatment plant.